EXPERIMEN PEMBUATAN CRAB NUGGET DENGAN BAHAN SECOND GRADE DARI INDUSTRI RAJUNGAN SERTA ANALISA ASPEK EKONOMINYA - muhammad yusuf; agus suyanto (Universitas Muhammadiyah Semarang, 2011)
Development value added crab of second grade still very has potency to be developed and marketed. One of the development effort tried by utilization crab become crab nugget. This research aim to study how far its development prospect and how its marketing strategy so that product of experiment became the best product. In other hand, crab nugget as alternative and new nugget in the market can provide opportunity of entrepreneurship. Research method uses experiment with presentation of data descriptively tabulation traverse (cross-tabs). Result of market survey, consumer response to fickle product of crab nugget is: (a) Respondent interested to product counted 88,3 % (b) Respondent enthusiastic buy product 73,3 % (c) Respondent interested to product but do not intend to buy counted 15 %. Strategy performed within effort improve sale done by : (a) give better service (b) multiply promotion effectively and smart (c) vie with image feel more pre-eminent (d) give freshment at sale place visited by consumer.